Brain responses in evaluating feedback stimuli with a social dimension - Zhang, Yuan; Li, Xiang; Qian, Xing; Zhou, Xiaolin (Frontiers in Human Neuroscience, 2012)
Previous studies on outcome evaluation and performance monitoring using gambling or simple cognitive tasks have identified two components of event-related potentials (ERPs) that are particularly relevant to the neural responses to decision outcome. The feedback-related negativity (FRN), typically occurring 200-300 ms post-onset of feedback stimuli, encodes mainly the valence of outcome while the P300, which is the most positive peak between 200-600 ms, is found to be related to various aspects of outcome evaluation. This study investigated the extent which neural correlates of outcome evaluation involving complex feedback stimuli (i.e., female faces) are similar to those revealed for simplex feedback. We asked participants to judge the attractiveness of blurred faces and then showed them unblurred faces as (implicit) feedback of their performance. The FRN effect can be identified by the ERP waveforms, albeit in a delayed 300-380 ms time window, with faces inconsistent with the initial judgment eliciting more negative-going responses than faces consistent with the judgment. However, the ERP waveforms did not show the typical pattern of P300 responses. With the principal component analysis (PCA), a clear pattern of P300 effects were revealed, with the P300 being more positive to faces consistent with the initial judgment than to faces inconsistent with the judgment and more positive to attractive faces than to unattractive ones. The feedback consistency effect on either the FRN or the P300 was unaffected by the attractiveness of the feedback faces. These findings suggest that brain responses involved in processing complex feedback stimuli with a social dimension are generally similar to those involved in processing simplex feedback stimuli in gambling or cognitive tasks, although appropriate means of data analysis are needed to reveal the typical ERP effects that may have been masked by sophisticated cognitive (and emotional) processes for complex stimuli.